Big Data and changes in audit technology: contemplating a research agenda. Issue 1 (2nd January 2019) - Salijeni, George; Samsonova-Taddei, Anna; Turley, Stuart
Abstract : This study explores the most recent episode in the evolution of audit technology, namely the incorporation of Big Data and Data Analytics (BDA) into audit firm approaches. Drawing on 22 interviews with individuals with significant experience in developing, implementing or assessing the impact of BDA in auditing, together with publicly available documents on BDA published within the audit field, the paper provides a holistic overview of BDA-related changes in audit practice. In particular, the paper focuses on three key aspects, namely the impact of BDA on the nature of the relationship between auditors and their clients; the consequences of the technology for the conduct of audit engagements and the common challenges associated with embedding BDA in the audit context. The study's empirical findings are then used to establish an agenda of areas suitable for further research on the topic. The study is one of the first empirical accounts providing a perspective on the rise of BDA in auditing.